Systematic search for peptide and protein ligands of human serum albumin capable of affecting its interaction with amyloid β peptide - E. V. Loktyushov; E. A. Litus; E. I. Deryusheva (Acta Biomedica Scientifica, 2022)
Background. Human serum albumin (HSA) is a natural buffer of amyloid-β peptide (Aβ), a key factor in the development of Alzheimer’s disease (AD). A promising approach to the AD prevention is to reduce the concentration of free Aβ by targeted stimulation of the interaction between HSA and Aβ. This approach can be implemented by increasing the affinity of HSA to Aβ through the action of HSA ligands, which was previously demonstrated for some low molecular weight ligands.   The aim of the study was to search for peptide and protein ligands of human serum albumin capable of affecting its interaction with Aβ.   Materials and methods. To perform a systematic search for peptides/proteins, HSA ligands that are capable of affecting Aβ-HSA interaction, we analyzed the DrugBank, BioGRID, and IntAct databases. As criteria for selecting candidates, along with physicochemical characteristics (molecular weight, solubility, blood-brain barrier passage, molar concentration), we used the requirements of extracellular proteins localization and strict association with AD, according to the DisGeNET and Open Targets Platform databases as well as Alzforum online resource. The algorithms for searching and analyzing the obtained data were implemented using the high-level programming language Python.   Results. A candidate panel of 11 peptides and 34 proteins was formed. The most promising candidates include 4 peptides (liraglutide, exenatide, semaglutide, insulin detemir) and 4 proteins (S100A8, transferrin, C1 esterase inhibitor, cystatin C).   Conclusions. Selected peptide and protein candidates are subject to experimental verification regarding their effect on the HSA-Aβ interaction and can become the basis for the development of first-in-class drugs for the prevention of Alzheimer’s disease.